Analisis kelimpahan E.coli dan bakteri Patogen sebagai indikator penurunan kualitas perairan pada budidaya keramba apung ikan patin desa Buluh Cina Kabupaten Kampar - Mumin Rifai; Zulkarnaini Zulkarnaini; Sofyan Husein Siregar (Pelantar Press, 2017)
The research on Escherichia coli (E. coli) and bacterial pathogens within catfish culture in Buluh Cina Village has been done in August 2015. This study aimed to analyze the quality of the river water, the abundance of E.coli in the water stream and pathogenic bacteria in catfish and to correlate the quality of the water with an abundance of E. coli and the prevalence of pathogenic bacteria. The location of the study is three observation stations with sampling conducted by three replications. The water quality parameters under investigation were temperature, brightness, pH, DO, Nitrate, Nitrite, Ammonia, Phosphate, TSS and BOD while the indicator for microbiological contamination is done by testing the abundance of E. coli in the river water as well as the pathogenic bacteria in catfish. The results of water quality measurements and testing of E. coli indicate the water quality is still good with the standard required under Regulation No 82/2001 except ammonia, phosphates, nitrites and E. coli. Ammonia has exceeded the threshold value with the average from 0.018 to 0.059 mg/L, the phosphate on the average value of 4,921 to 9,804 mg/L, nitrite in the average value from 0.015 to 0.068 mg/L and the abundance of E. coli on the value of the average 4,200-5,500 cfu / 100 ml. While the results of testing on pathogenic bacteria found in catfish are Aeromonas sp, Pseudomonas sp, Pasteurella sp and Edwardsiella sp. The highest prevalence of pathogenic bacteria obtained in Aeromonas sp is equal to 29.63%. In the statistical test toward chemical parameters of water measured affects the abundance of E. coli by 94%. The most significant variable on the water quality parameters affecting the abundance of E. coli is the temperature, TSS, pH, and DO with a correlation coefficient lebih dari 0.5.